Implementasi Lesson Study Pada Mata Pelajaran Ekonomi Untuk Meningkatkan Motivasi Belajar Siswa - Nurul Faizah; Imam Mukhlis; Chusnul Chotimah (Jurnal Pendidikan Ekonomi)
Learning motivation is the behavior of students who show interest and willingness in academic performance and critical thinking at school. Learning situations that are carried out in learning activities sometimes experience disruption such as students who are less focused, daydreaming and low learning motivation of students, low learning motivation will reduce student learning outcomes, so this study aims to determine the impact of implementing lesson study on economic subjects. to increase student motivation in class XI IPS 2 MAN 1 Malang City. The students involved were 40 people, with one model teacher, one supervisor, one tutor teacher, and 4 observers. This research uses the lesson study method to analyze the problem of the low learning motivation of students. The learning activity uses a scientific learning approach and the talking stick learning model. Lesson study stages are plan, do, see. The results of the study concluded that the learning motivation of students has increased with the implementation of lesson study activities.DOI: https://dx.doi.org/10.17977/UM014v13i22020p133